Memahami Makna Ijazul Ilmi dalam Fenomena Air Laut yang Terdapat dalam Surah Arrahman Ayat 19 - Abdul Bukhori Hafis; Hanafi Nasution Mahathir; Muhammad Hutasuhut (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The discourse regarding al-i'jaz al-'ilmi is a contemporary issue in the i'jaz al-Qur'an, especially if it is related to the discourse on the integration of science and religion. This is in line with the view that the Qur'an contains al-i'jaz al-'ilmi, so that it provides motivation and guidance for the development of science. However, errors in integrating science and religion will give birth to